Cardiac rehabilitation of Baduanjin exercise in coronary heart disease after PCI: A protocol for systematic review and meta-analysis of randomized controlled trials. Issue 15 (16th April 2021) - Li, Xing-Xing; Fan, Zong-Jing; Cui, Jie; Lin, Quan; Zhuang, Rui; Liu, Rong-Peng; Wu, Yang
Abstract: Background: Percutaneous coronary intervention (PCI) is an effective revascularization strategy in patients with coronary heart disease (CHD). However, recent studies had indicated that postPCI patients usually suffer from a low-quality life. Cardiac rehabilitation (CR) has been recommended by numerous guidelines in the clinic for these patients. And Baduanjin exercise can significantly benefit patients with CHD. Regrettably, the effect of Baduanjin exercise on postPCI patients is still not clear. Therefore, this systematic review and meta-analysis protocol is planned to explore the effect of Baduanjin exercise in patients with CHD who have undergone PCI. Methods: PubMed, Excerpta Medica Database, Cochrane Library, Web of Science, Wanfang Database, SINOMED, China Science and Technology Journal Database, and China National Knowledge Infrastructure will be searched for appropriate articles from respective inceptions until December 1th, 2020. Two reviewers will independently conduct article selection, data collection, and risk of bias evaluation. Disagreements will be resolved first by discussion and then by consulting a third author for arbitration. The primary outcome will include left ventricular ejection fraction. And the change in the scores on the Seattle Angina Questionnaire, SF-36 health survey scale, Zung Self-rating Anxiety scale and self-rating depression scale will be used as the secondary outcomes. RevMan 5.3 will be used for meta-analysis. Results: This systematic review and meta-analysis will explore whether Baduanjin exercise is an effective intervention in postPCI patients. Conclusion: This systematic review and meta-analysis will provide convincing evidence of Baduanjin exercise that specifically focuses on CR of Baduanjin exercise on CHD after PCI. Registration number: INPLASY202130065.